Engineering properties of IN-100 alloy. (Nickel Institute, 1968)
IN-100 alloy is a nickel-base precipitation hardenable, vacuum cast alloy possessing high rupture strength through 1900 °F. The high percentages of aluminum and titanium and the low refractory metal content make IN-100 particularly attractive on strength to density basis. The alloy has been successfully cast and utilized in a variety of shapes from turbine blades, vanes and nozzles to integral wheels. This publication provides various engineering properties of IN-100 Alloy.
Keywords: Nickel alloys.; elektronické knihy; electronic books